Detection of adhesion molecules on inflamed macrophages at early-stage using SERS probe gold nanorods - Dakrong Pissuwan (2018)
© The Author(s) 2016. In recent years, it has been shown that inflammatory biomarkers can be used as an effective signal for disease diagnoses. The early detection of these signals provides useful information that could prevent the occurrence of severe diseases. Here, we employed surface-enhanced Raman scattering (SERS) probe gold nanorods (GNRs) as a tool for the early detection of inflammatory molecules in inflamed cells. A murine macrophage cell line (Raw264.7) stimulated with lipopolysaccharide (LPS) was used as a model in this study. The prepared SERS probe GNRs containing 4-mercaptobenzoic acid as a Raman reporter to generate SERS signals were used for detection of intracellular adhesion molecule-1 (ICAM-1) in macrophages after treatment with LPS for varying lengths of time. Our results show that SERS probe GNRs could detect significant differences in the expression of ICAM-1 molecules in LPS-treated macrophages compared to those in untreated macrophages after only 1 h of LPS treatment. In contrast, when using fluorescent labeling or enzyme-linked immunosorbent assays (ELISA) to detect ICAM-1, significant differences between inflamed and un-inflamed macrophages were not seen until the cells had been treated with LPS for 5 h. These results indicate that our SERS probe GNRs provide a higher sensitivity for detecting biomarker molecules in inflamed macrophages than the conventional fluorescence and ELISA techniques, and could therefore be useful as a potential diagnostic tool for managing disease risk.